Nell'ombra di Dio (Materiali di Estetica. Terza serie, 2019)
In March 2017, the Fondazione Corrente in Milan hosted a round of "Esthetic Conversations" every Wednesday, organized by Roberto Diodato, Elio Franzini, Fulvio Papi and Gabriele Scaramuzza. The cycle ended with a meeting held by Gabriele Scaramuzza and Sabrina Peron, titled The Remains of God, during which the theme of God's existence in the world of culture was tackled, starting from the reflection of the unthinkability of this World without cathedrals, prayer, religious practices, and treatises of theology. Moving from the philosophy of Banfi's religion, confrontation has widened to broader reflections that included Dostoevsky, Mann, Bulgakov and Yourcenar, and the eternal conflict between good and evil. This work is my report to the conference, while Gabriele Scaramuzza's presentation is being published in Filosofia e Teologia.